Analysis of Knowledge and Cognitive Domain on Indonesia Secondary School Curriculum Year 1984-2013 - Yanti Herlanti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Indonesia introduced some curriculum with a constructivist approach since 1984. Every ten years, the curriculum documents developed according to the needs of learners and contemporary. This study aimed to analyze the cognitive and knowledge domain according the curriculum in Indonesia. Curriculum documents analyzed were 1984, 1994, 2006, and 2013 particularly subjects Biology. Knowledge and cognitive domains based on the revised Bloom's Taxonomy.  Knowledge aspect consists of factual knowledge, conceptual, procedural, and metacognitive.  Cognitive aspect consists of remembering, understanding, applying, analyzing, evaluating, and creating. The analysis showed 2013 curriculum want to develop higher order thinking than other curriculum.Keywords: knowledge, cognitive, curriculum, Indonesia